ANALISIS PENGARUH PERSEPSI HARGA TERHADAP PERILAKU PEMBELIAN PRODUK KEBUTUHAN SEHARI-HARI (STUDI PADA INDO GROSIR JALAN MAGELANG) - Wirawan Seto Putro (Journal Competency of Business, 2019)
This empirical research is intended to determine the relationship between consumer perceptions of the role of negative prices (Value Consciousness, Price Consciousness, Coupon Proneness, Sale Proneness, and Price Mavenism) with the role of positive prices (Price Quality Schema and Prestige Sensitivity). In this study the data were obtained through distributing questionnaires to 250 respondents, namely consumers who were making a purchase or those who had made a purchase at Indogrosir Jalan Magelang Yogyakarta. Based on the results of data analysis with SEM analysis with the AMOS program showed that there was an influence of negative variables. role price on positive role price, there is a negative role price influence on Value Consciousness in the role of negative prices, there is a negative role price influence on Price Mavenism on the role of negative prices, there is a negative influence role price on Price Consciousness on the role of negative prices, there is a negative role effect price on Sale Proneness on the role of negative prices, there is a negative influence on the role price on Coupon Proneness on the role of negative prices, there is a positive influence on the role price on Price quality schema on the role of negative prices and there is a positive influence on the role price against Prestige sensitivity.